ANALISIS NILAI TAMBAH KELAPA MENJADI MANISAN KELAPA (STUDI KASUS: USAHA ALFIS) DI DESA SIMPANG LHEE KECAMATAN LANGSA BARAT KOTA LANGSA - Septarida, Taslya; Alham, Fiddini; Mahyuddin, Thursina (Jurusan Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Mataram, 2024)
This study aims to analyze the amount of profit and added value from coconut intocandied coconut in Simpang Lhee Village, West Langsa District, Langsa City byusing a purposive sampling method. The research method was carried outpurposively with a case study research design. The collection of data used isprimary data and secondary data. The population and sample used is only 1sample, namely the business owner and entrepreneur of coconut into candiedcoconut which has a business name, namely Alfis Enterprises. This research wasconducted in one of the villages in the Langsa sub-district, namely Simpang LheeVillage. To find out the amount of profit and added value from coconut intocandied coconut in Simpang lhee Village, West Langsa District, Langsa City,using the profit data analysis method and the added value analysis method usingthe Hayami method. The results of this study indicate that the amount of revenueobtained from the sales of candied coconut products is Rp. 10,000,000.00. Thetotal costs incurred during the production process amounted to Rp. 3,663,887.00and the profit gained during the production process is Rp. 6.336,113.00.